The Effect of Halal Product Exports and Gross Domestic Product on Current Account Balance in Indonesia - Habsyah, Ade; Kartika, Irina; Panorama, Maya (Jurnal Manajemen (Edisi Elektronik), 2025)
This study aims to analyze the effect of Halal Product Exports and Gross Domestic Product on Indonesia's Current Account Balance. The research focuses on understanding how the halal industry and macroeconomic growth contribute to the dynamics of external economic stability. Using a quantitative approach, this study employs time series data from 2010 to 2024, analyzed through econometric methods including the Augmented Dickey-Fuller (ADF) test, Granger Causality Test, Cointegration Test, and Autoregressive Distributed Lag (ARDL) model, processed with EViews version 12. The findings reveal that Halal Product Exports have a significant positive effect on the Current Account Balance, whereas Gross Domestic Product shows no significant direct impact. These results suggest that promoting halal product exports could serve as a strategic policy to strengthen Indonesia's external economic position. This study provides insights for policymakers in enhancing export diversification strategies and sustaining economic resilience